Rumours, myths, and misperceptions as barriers to contraceptive use among adolescent girls and young women in South Africa - Jonas, Kim; Duby, Zoe; Maruping, Kealeboga; Harries, Jane; Mathews, Catherine (Frontiers in Reproductive Health, 2022)
Background: Rumours, myths and misperceptions about contraceptives are a barrier to contraceptive use in general but more so among adolescent girls and young women (AGYW). As rumours and misinformation disseminate easily, it is important to explore how they affect uptake of contraceptives among AGYW at risk of unintended pregnancies. This study used qualitative methods to explore whether rumours, myths and misperceptions about contraceptives remain barriers to modern contraceptive use among AGYW who were beneficiaries of a combination HIV prevention intervention in South Africa. Methods: Four (4) once-of in-depth interviews (IDIs), 53 serial in-depth interviews (SIDIs) and 19 focus group discussions (FGDs) with 185 AGYW aged 15-24 years living in five of the ten intervention districts were conducted as part of the HERStory 1 Study. Interviews and FGDs were audio recorded and data were analyzed thematically, aided by Nvivo 12 software. Results: Rumours, myths and misperceptions about contraceptives, as well as socio-cultural norms regarding contraception significantly hinder AGYW’s use of modern contraceptives. Peer/friends’ disapproval, parents’ and boyfriend’s lack of support for AGYW’s use of contraceptives, based on rumours and perceived side effects also impede AGYW’s access and use of contraceptives. Conclusion: Sexual and reproductive health (SRH) programs could address social norms that disapprove of contraception, and target rumours, myths and misperceptions regarding modern contraceptive methods through educational campaigns and community engagements. Promoting contraception in the community, and men’s acceptance of contraceptive use, in particular, may increase their understanding of modern contraceptives and subsequently, their approval for their partners/girlfriends to use them.